Modification of turbulent wake characteristics by two small control cylinders at a subcritical Reynolds number - Yan, T. (2019)
In this paper, the flow around a main circular cylinder with two small control cylinders is numerically investigated at a subcritical Reynolds number of 3900. Two small control cylinders with diameter ratio of d/D = 0.04 (d and D are the diameters of the control cylinders and the main cylinder, respectively) are symmetrically placed inside the separated shear layers emanating from the main cylinder. The computation is performed with highly resolved direct numerical simulations employing a high-order spectral/hp element method. For validation purposes, the results of the flow over a single cylinder are presented at first, and the current simulation is in good agreement with the existing experiments and large eddy simulations. For the main cylinder with the two control cylinders, the dynamics of shear layers is found to be modified strongly owing to the disturbance from the small control cylinders. As a consequence, the recirculation length is decreased by 89% as compared to that of a single cylinder. The presence of the small control cylinders further leads to a significant increase in the fluctuating lift and the mean drag exerting on the main cylinder. Furthermore, the statistical analysis and turbulent wake visualization imply that the turbulent intensity is amplified in the near wake region and becomes weaker further downstream. This study then suggests that the small control cylinders located in the near wake region of the main cylinder may work differently in the turbulent wake against that in the laminar wake.